“BLACK IS BEAUTIFUL” HANS-JÜRGEN MASSAQUOI’S PROVERBIAL AUTOBIOGRAPHY DESTINED TO WITNESS (1999) - Mieder, Wolfgang (Proverbium - Yearbook, 2022)
Hans-Jürgen Massaquoi’s (1926-2013) autobiography Destined to Witness. Growing up Black in Nazi Germany (1999) appeared simultaneously in German translation as Neger, Neger, Schornsteinfeger. Meine Kindheit in Deutschland (1999, 2006 as a film). The bestseller recounts Massaquoi’s birth in 1926 at Hamburg as a biracial child of a German mother and a black father from Liberia who returns to Africa leaving his wife and Afro-German son to fend for themselves in a working-class neighborhood. Their struggle to survive Nazi Germany is described in numerous small chapters that are informed by the journalistic as well as literary style that Massaquoi became accustomed to once he became established in the United States as managing editor of the African American magazine Ebony. The book is replete with proverbs and proverbial expressions that add metaphorical expressiveness to this emotional and informative account of survival among prejudice, stereotypes, and racism. Many of the proverbs, often quoted by Massaquoi’s mother, are cited in German with English translations or only in English. Thus the book is a telling example of how proverbs function in a family and beyond as social strategies to carve out a marginalized existence between 1926 and the early 1950s in Germany, Liberia, and the United States. Numerous contextualized references are cited, and there is also a large index of 509 (645 counting 136 duplicates) proverbial texts